Highly pathogenic avian influenza A H5N1 and pandemic H1N1 virus infections have different phenotypes in Toll-like receptor 3 knockout mice - Leung, Y. H. Connie (Society for General Microbiology, 2014)
Toll-like receptors (TLRs) play an important role in innate immunity to virus infections. We investigated the role of TLR3 in the pathogenesis of H5N1 and pandemic H1N1 (pH1N1) influenza virus infections in mice. Wild-type mice and those defective in TLR3 were infected with influenza A/HK/486/97 (H5N1) or A/HK/415742/09 (pH1N1) virus. For comparison, mice defective in the gene for myeloid differential factor 88 (MyD88) were also infected with the viruses, because MyD88 signals through a TLR pathway different from TLR3. Survival and body weight loss were monitored for 14 days, and lung pathology, the lung immune-cell profile, viral load and cytokine responses were studied. H5N1-infected TLR3(−/−) mice had better survival than H5N1-infected WT mice, evident by significantly faster regain of body weight, lower viral titre in the lung and fewer pathological changes in the lung. However, this improved survival was not seen upon pH1N1 infection of TLR3(−/−) mice. In contrast, MyD88(−/−) mice had an increased viral titre and decreased leukocyte infiltration in the lungs after infection with H5N1 virus and poorer survival after pH1N1 infection. In conclusion, TLR3 worsens the pathogenesis of H5N1 infection but not of pH1N1 infection, highlighting the differences in the pathogenesis of these two viruses and the different roles of TLR3 in their pathogenesis.